2017
DOI: 10.1080/19490976.2016.1278105
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbial transplantation as a therapeutic option in patients colonized with antibiotic resistant organisms

Abstract: Despite increasing interest in fecal microbiota transplantation (FMT), its full therapeutic potential has yet to be determined. Since its increase in popularity, FMT has been shown to be highly effective in the treatment of both Clostridium difficile infection (CDI) and its recurrent form. Interest in FMT now expands well beyond the treatment of CDI to other processes with known associations to the microbiota such as antibiotic resistant infections, inflammatory bowel disease (IBD), hepatic encephalopathy, neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Moreover, antibiotic therapies during CDI treatment may promote the expansion of antibiotic-resistant organisms (AROs) such as vancomycin-resistant Enterococci (VRE) [12,13]. On the other hand, intestinal microbiota restoration has shown to be effective for CDI treatment as well as the restoration of colonization resistance against C. difficile and AROs [14,15]. Indeed, intestinal microbiota restoration has become a commonly performed investigational therapy for rCDI with decent success rates [8,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, antibiotic therapies during CDI treatment may promote the expansion of antibiotic-resistant organisms (AROs) such as vancomycin-resistant Enterococci (VRE) [12,13]. On the other hand, intestinal microbiota restoration has shown to be effective for CDI treatment as well as the restoration of colonization resistance against C. difficile and AROs [14,15]. Indeed, intestinal microbiota restoration has become a commonly performed investigational therapy for rCDI with decent success rates [8,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Initial case reports indicated that several types of multidrug-resistant opportunistic organisms such as carbapenemase- and extended-spectrum β-lactamase (ESBL)–producing Enterobacteriaceae, vancomycin-resistant Enterococci, and methicillin-resistant Staphylococcus aureus were being eliminated in patients undergoing FMT for recurrent CDI [ 5 ]. Shortly thereafter, case reports began emerging using FMT to directly decolonize non-CDI patients with resistant infections or patients at risk of infection [ 5 , 6 ]. A recent study showed complete decolonization of various organisms in 15 of 20 (70%) patients [ 7 ].…”
mentioning
confidence: 99%
“…Through the recolonization of normal microbes, FMT is also believed to play a role in competitive exclusion of gastrointestinal pathogens, where beneficial microbes outcompete pathogens for adhesion, attachment, and infection (Collado et al, 2007;Khoruts and Sadowsky, 2016). Recently, FMT has also been anecdotally recognized as a potential therapy for those human patients infected with multidrug resistant bacteria, such as methicillin-resistant Staphylococcus aureus and vancomycin-resistant Enterococcus faecalis (Cohen and Maharshak, 2017;Laffin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%